PNRR Mask (diségno, 2025)
On 2 and 3 May 2025, the day of studies and public activities took place in Lipari, at the Archaeological Park of the Aeolian Islands and the Luigi Bernabò Brea Regional Archaeological Museum (fig. 1), as part of the project Restituzione alla teatralità delle miniature di maschere rituali nella necropoli di Lipari, funded by the PNRR (NextGenerationEU). [read more]